Severely Scarred Oronasal Cleft Defects in Edentulous Adults: Initial Data on the Long-Term Outcome of Telescoped Obturator Prostheses Supported by Zygomatic Implants. (July 2013) - Landes, Constantin A.; Ghanaati, Sharam; Ballon, Alexander; Thai, Van Dung; Reinhard, René; Nolte, Dieter; Piwowarczyk, Andree; Wagner, Mathias; Sader, Robert
Objective: Prosthetic rehabilitation of edentulous patients presenting with severely scarred oronasal cleft defects. To document the outcome of telescopic obturator prostheses attached to zygomatic implants in edentulous cleft lip and palate patients. Patients and Methods: Four edentulous patients suffering from the consequences of cleft lip and palate were selected from a cohort of 52 patients who had received zygomatic implants between 1998 and 2010. Oronasal communication had persisted and severe scars and chronic infection were noted in the cleft region. Bone grafting procedures were contraindicated due to high risk for dehiscence. For the functional support of telescopic prostheses, nine zygomatic implants and two standard dental implants had been placed. Results: The zygomatic implants and the telescopic prostheses survived an average of 62 months (37 to 99 months) and were successful. Patients' satisfaction and oral function improved (on visual analog scale and oral health impact profile). Conclusions: Telescopic obturator dentures supported by zygomatic implants represent a feasible option for the prosthetic rehabilitation of cleft lip and palate patients with severe impairments of the edentulous ridges including atrophy, scar tissue, ridge defects, oronasal communication, and chronic infection in the cleft region.